Multimodal Analysis on The Cultural Content of Indonesian High School English E-Textbooks - Denatasa Permatasari (ENLIT, 2022)
The pedagogy of English-Language Teaching (ELT) has highlighted the close connection between language and culture. In the educational setting, teaching and learning materials are linked to the introduction of culture, which is represented through language, particularly in English language material. The findings of this paper provide Indonesian English teachers with new insights into the presence of cultural value in the English textbooks used. Unquestionably, the inclusion of various cultures in the textbook may help teachers and students become more aware of their own cultures as well as develop a better understanding of the existence of other cultures. The cultural content of High school Indonesian English e-textbooks was analyzed using multimodal analysis. The framework used in this project is based on Stec's work on categorizing as well as Cortazi and Jim's (1999) work. It is discovered that there is an imbalance between the source culture, the target culture, and the international culture as a result of the cultural content in Indonesian high school e-textbooks. Nevertheless, when compared to other cultures, the source culture is more dominant. Students are expected to be more aware of their culture after reading input texts that expose surface cultures. It could validate the idea that using relevant, culturally relevant content is crucial when teaching the target language.